(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Anemia in pregnancy is a problem that requires special treatment because its prevalence is still high. Factors that influence the incidence of anemia in pregnant women include the age of the pregnant woman, parity, education, economic level, ANC visits and compliance with the consumption of Fe tablets. Objective: to determine the factors that influence the incidence of anemia in pregnant women at the Muara Harus Health Center. Method: This type of research uses quantitative research methods. The design used is descriptive with a cross sectional approach. The sampling technique is total sampling. The analysis used is the chi-square test. Results: Mothers with an age risk of anemia were 43.7%, p value 0.581 > 0.05. Parity has a risk of anemia 37.5% p value 0.497 > 0.05. Education level p value 0.344 > 0.05. Low economic level 71.8% p value 1.000 > 0.05. Compliance with ANC visits was 37.5%, p value 0.017 <0.05. Compliance with fe tablet consumption was 46.8% p value 0.037 <0.05. Conclusion: There is no statistically significant relationship between pregnant women’s age, parity, education level, economic level and anemia in pregnant women at the Muara Harus Community Health Center. There is a statistically significant relationship between compliance with ANC visits and compliance with fe tablet consumption on the incidence of anemia.